A Modified Survey of Reading Strategies (SORS) - a Good Instrument to Assess Students’ Reading Strategy Use - Thuy, Nguyen Thi Bich (VNU Journal of Foreign Studies; Vol 32 No 4, 2016)
Abstract: Reading comprehension is one of the most important factors in English language learning for all students because it provides the basis for a substantial amount of learning in education [1, 2]. Being aware of the importance of reading strategies and their impact on language learning researchers all over the world have taken a lot investigations into this field. This paper is an attempt to synthesize the most popular approaches to categorize reading strategies and proposes an effective instrument to assess students’ reading strategy use.